Assessing knowledge-transfer in sanitation projects to promote sustainable VIP latrine provision - Ngobeni, Lulama Ntombana (Department of Information Systems, 2016)
The aim of this study was to assess how knowledge transfer through community engagement and public participation can be used to support the sustainability of VIP latrines, and hence address the negative perceptions that people have of the VIP latrine. In South Africa, the basic minimum acceptable level of sanitation is a lined Ventilated Improved Pit (VIP) latrine. Some sanitation projects utilising VIP latrines have, however, been unsuccessful as a result of the poor construction and design practices, and insufficient buy-in from latrine users. Successful VIP latrine sanitation projects have shown to use effective knowledge transfer through community engagement. The study comprises of a review of literature on community engagement, public participation, sustainable sanitation, VIP latrines and the transfer of knowledge in sanitation projects. The fieldwork study was a comparative assessment of two VIP sanitation projects implemented in the Bushbuckridge Local Municipality: a project coordinated by an NGO appointed by the Department of Human Settlements as part of the Rural Household Infrastructure Programme; and another where the project was run by a project management firm appointed by the local municipality which used funding from the municipal infrastructure grant. For the NGO co-ordinated project, a community engagement approach was adopted, whilst the Project Management Firm co-ordinated project used a public participation approach. The projects were implemented in two villages both situated 10km North East of the town of Bushbuckridge. The comparative assessment was two-fold: an assessment of the sustainability of the VIP latrines, using the Integrated Assessment of Sustainable Development which was developed by Krajnc and Glavic (2004), and a Critical Systems Heuristics (CSH-developed by Ulrich in 1983) (Reynolds, 2007) analysis of the public participation and community engagement methods used in both projects.